Numerical analysis of blood flow in abdominal aortic aneurysm using finite volume method - Fatahillah, Arif; Anggraini, Azza Liarista; Setiawani, Susi (Universitas Islam Negeri Raden Intan Lampung, 2022)
There is a deadly cardiovascular disease that can cause swelling of the Abdominal Aorta. This disease is known as Abdominal Aortic Aneurysm (AAA). AAA is believed to be a degenerative process caused by genetic factors, gender, body weight, and age. Changes in collagen and elastin in the aortic wall are the cause of the degeneration process. Therefore, it will cause dilatation of the aortic wall. Swelling of the aortic blood vessels will affect the blood flow velocity in the aortic blood vessels. This research aims to analyze the velocity of blood flow in the Abdominal Aortic Aneurysm based on swelling diameter, proximal neck length, and aneurysm channel length using Computational Fluids Dynamics (CFD). The blood flow velocity was modeled using mathematical language based on mass continuity equations and momentum equations. Then the finite volume method was one method to solve the mathematical model. MATLAB and ANSYS FLUENT software were used to simulate the velocity of blood flow analysis. The results of the research were shown that the larger the diameter and swelling channel length, the smaller the velocity of blood flow produced. Then, the greater the length of the proximal neck, the faster the resulting blood flow will be.